Ethics in Health Research - Wikler, Daniel (Encuentro, 2010)
That medical research with human subjects presents ethical issues and problems is well known. I will talk about some of these in what follows. But it is worth emphasizing beforehand that if there is one overwhelming problem involving research that is of great of ethical importance, it is that there is not enough research. So the purpose of this presentation is not to point to ethical problems in research in order to discourage research. It is exactly the opposite: it is because of the importance of research that we want to make sure that our purpose is not blocked by ethical problems which we could have avoided if we thought about these things well before hand.